2021
DOI: 10.2196/23059
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Tracker Information and Privacy Management: Empirical Study

Abstract: Background Fitness trackers allow users to collect, manage, track, and monitor fitness-related activities, such as distance walked, calorie intake, sleep quality, and heart rate. Fitness trackers have become increasingly popular in the past decade. One in five Americans use a device or an app to track their fitness-related activities. These devices generate massive and important data that could help physicians make better assessments of their patients’ health if shared with health providers. This u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Surprisingly, the effect is not significant. This contradicts previous research that the risks of telehealth are threats to telehealth usage [ 17 , 56 ]. A possible explanation is that the risks listed in the questionnaire survey are not persuasive enough to significantly reduce the expected value obtained from telehealth.…”
Section: Empirical Analysis and Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Surprisingly, the effect is not significant. This contradicts previous research that the risks of telehealth are threats to telehealth usage [ 17 , 56 ]. A possible explanation is that the risks listed in the questionnaire survey are not persuasive enough to significantly reduce the expected value obtained from telehealth.…”
Section: Empirical Analysis and Discussioncontrasting
confidence: 83%
“…Nevertheless, insecurity does not have a significant negative impact on perceived value. Whilst ample research has identified that risks of telehealth can prohibit users from accepting the telehealth [ 56 ], the result of this research indicates that during the health crisis, the benefits of telehealth are becoming more evident; in this case, risks that cause fewer concerns may not significantly lower users' perceived value of telehealth. Further, attitude partially mediates the effect of perceived value on the acceptance of telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the use of wearables can modify habits such as excessive time spent sitting, unlike happens with other habits that may require a more complex elaboration, such as carrying out a physical activity program or modifying the diet according to health standards. If the registered information of the devices was managed by healthcare professionals, it could provide wider benefits to users [7,58]. Health professionals can advise on behavioral change techniques and recommendations to guide their use.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the characteristics of the information they collect, they can be an exhaustive source of information on the health habits of the population that can be shared with health professionals and serve as a diagnostic tool on the quantity and quality of physical activity as well as other health-related habits such as the quantity and quality of sleep. However, most of the time, the population uses wearable activity tracker devices, but does not necessarily share the information obtained with professionals who can help them with interpretation and making it effective [7]. Sharing data from wearable devices with healthcare professionals would allow them to better understand their patients' habits [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation